A qualitative study of noise sensitivity in adults with autism spectrum disorder. (December 2016) - Landon, Jason; Shepherd, Daniel; Lodhia, Veema
Highlights: Adults with ASD identified anxiety as a key component of their noise sensitivity. Coping responses were largely avoidant or escape oriented, and less problem-focussed than in some other clinical populations. Clinical efforts should focus on planned problem-focussed approaches to coping, and ameliorating anxiety. Abstract: Background: Individuals with autism spectrum disorder (ASD) may respond to environmental stimuli more intensely and less conventionally than typical peers. Research has generally focused on sensory sensitivity broadly, rather than individual modalities. Thus, experiences of noise sensitivity (NS) have not been specifically documented in detail. This study documents the experiences of NS in adults with ASD. Method: Semi-structured interviews were undertaken and recorded with 10 participants. The resultant data were analysed using a descriptive thematic approach to summarise the patterns in the participants' experiences. Results: The analysis identified four themes emphasising the unique way those with ASD experience sound, and the impacts of noise sensitivity on them. Conclusions: Documenting experiences such as these is an important early step towards a better understanding and hence supporting those negatively experiencing sound. The present results are both useful for those affected and those working with them, in terms of developing improved methods of coping and clinical interventions. The results are also consistent with recent neurophysiological research.